Fruit Morphological Characters of Durian in Ra-Ngae District Narathiwat Province - Ratwai, Thasanee; Keawchai, Jesada (Princess of Naradhiwas University Journal, 2019)
This research aimed to study fruit morphological characters of local durian in Ra-Ngae District, Narathiwat Province. The morphological characters were as follows: size, shape, spine, texture color, seed, and taste. The 60 samples were collected from the farmer’s farm in Ra-Ngae District, Narathiwat Province. The percentage, mean, maximum, minimum, and standard deviation were calculated. The results found that the average fruit weight, average fruit long, and average fruit wide were 1.25 kilograms, 51.62, and 45.64 centimeters, respectively. The fruit was found in round shape and the average fruit stalk was 5.0 centimeters long. The spine was curve shape with 4.8 centimeters long and 26.78 spines per square inch. The complete texture section was 4.27 per fruit. The color of fruit seed was light brown and 8.64 seeds per fruit. The color texture was light yellow with scale of the soft and luscious were 2.45 and 2.91, respectively. The scale of fiber texture, creamy, sweet, bitter, smell, and the taste were 3.16, 3.41, 3.07, 2.52, 3.41, and 3.02, respectively. The good characters of local durian from this research may be selected for breeding in the future.